ANALISIS PENGARUH IKLAN TELEVISI TERHADAP PURCHASE INTENTION PRODUK HONDA BEAT ESP DENGAN ENDORSER SEBAGAI VARIABEL MODERATING - Aditya Christianto Rahardjo (Jurnal Strategi Pemasaran, 2015)
This study discusses the influence of advertising that affect in purchase intention on the Honda Beat ESP with the endorser as an moderating variable. This research using quantitative research methods with the causal approach. There are four variables studied, including television ads as an independent variable, purchase intention is the dependent variable. And endorser as an intervening variable. The method used is using path analysis with SmartPLS 3.2 tools. Sample size was 100 respondents were at least 2x already watch ads Honda Beat ESP and respondents who have purchased a Honda Beat.